2023
DOI: 10.1002/qre.3262
|View full text |Cite
|
Sign up to set email alerts
|

A fatigue reliability assessment approach for wind turbine blades based on continuous time Bayesian network and FEA

Abstract: Wind turbine blades made by composite materials (CWTBs), encounter fatigue failures, such as cracks, fractures, delamination, etc. Finite Element Analysis (FEA) is applied for fatigue performance simulations of CWTBs as the full-scale testing is costly. To consider correlated failures and uncertainties in load and material parameters, this paper proposes a fatigue reliability assessment method based on continuous time Bayesian network and FEA. Specifically, the dangerous regions of each component of CWTBs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The time-varying degradation failure threshold 𝜎 0 − 𝜎 𝐻 is obtained by transposing Equation (7), so the following is a formulation of the gear degradation failure probability model for tooth surface contact fatigue…”
Section: Description Of Degradation Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The time-varying degradation failure threshold 𝜎 0 − 𝜎 𝐻 is obtained by transposing Equation (7), so the following is a formulation of the gear degradation failure probability model for tooth surface contact fatigue…”
Section: Description Of Degradation Failurementioning
confidence: 99%
“…He 3–6 employed the Bayesian network to examine the failure rate and reliability model of offshore wind turbines and extended the traditional failure mode and effect analysis method to explore the causes of structural failure suffered by wind turbines and develop their targeted maintenance strategies. Liu 7 analyzed the reliability of wind turbine blades based on Bayesian and finite element analysis. Sun 8 proposed a failure analysis method of the D‐vine copula Bayesian Network, which quantifies the probability of risk.…”
Section: Introductionmentioning
confidence: 99%
“…9 Liu et al proposed a fatigue reliability assessment approach for wind turbine blades that combines finite element analysis to identify critical regions and quantify uncertainties with a continuous time Bayesian network model to analyze failure probabilities and relationships between blade components. 10 When estimating the structural reliability of fatigue crack growth in aero-disks, the probabilistic model of the aero-disk is typically integrated with reliability analysis methods, such as First Second Moment Method (FORM), Monte Carlo Simulation (MCS) and Kriging Surrogate Model and others. Walz and Riesch established a stochastic model of turbine disk fracture failure based on probabilistic fracture mechanics, which solved both the failure probability of the disk and the sensitivity of input random parameters through a primary reliability method and MCS.…”
Section: Introductionmentioning
confidence: 99%
“…8 Finite element analysis is the primary tool for dynamic response and reliability analysis of pipelines. [9][10][11][12] For instance, Jing et al 13 created a model of a buried pipeline subjected to square rockfall impact and simulated the pipeline's dynamic response during rockfall, concluded that the impact duration was short, lasting only from 10 −3 to 10 −2 s. Gucuyen et al 14 established a test platform to investigate the impact loads on pipelines. The platform is equipped with a dynamic force sensor to analyze the dynamic response process and the changes in mechanical properties of pipelines made of different materials during rockfall and earthquake events.…”
Section: Introductionmentioning
confidence: 99%
“…Finite element analysis is the primary tool for dynamic response and reliability analysis of pipelines 9–12 . For instance, Jing et al 13 .…”
Section: Introductionmentioning
confidence: 99%